A facile approach for preparation of highly dispersed platinum-copper/carbon nanocatalyst toward formic acid electro-oxidation. (1st February 2016) - Huang, Yiyin; Zhao, Tianshou; Zeng, Lin; Tan, Peng; Xu, Jianbo
Graphical abstract: Highlights: Solid phase evolution was used to prepare binary metal catalyst. Big PtCu particles were evolved into small alloy nanoparticle after acid etching. Solid phase evolution helped high dispersion of particles relative to co-reduction. FAO activity of PtCu/C increased by a factor of 1.5–2.0 compared to Pt/C. CO oxidation peak on PtCu/C shifted ca. 70 mV relative to Pt/C and PtCu/C (C). Abstract: Gaining control over the size and dispersion of binary metal nanoparticles is critical in order to manipulate their catalytic properties. In this study, we demonstrate a facile and effective solid phase evolution approach to prepare a highly dispersed PtCu/C catalyst via a surface substitution and etching separation process with the Pt-decorated Cu particles on carbon as the precursors. It is demonstrated that the dispersion of metal nanoparticles in PtCu/C derived from the present solid phase evolution is better than that in PtCu/C (C) prepared from the co-reduction by NaBH4 . As a result, the synthesized PtCu/C shows a larger electrochemically active surface area (ECSA) (48.6 m 2  g −1 ), higher mass (0.52 mA μg −1 ) and area activities (1.07 mA cm −2 ) than that of the PtCu/C (C) (37.9 m 2  g −1, 0.34 mA μg −1 and 0.89 mA cm −2, respectively). As compared to commercial Pt/C catalyst, PtCu/C exhibits ca. 2.5 times higher formic acid oxidation (FAO) activities (0.52 mA μg −1 and 1.07 mA cm −2 ). The tolerance toward CO poisoning is characterized by CO stripping, the result indicates that both onset (0.43 V) and peak (0.50 V) potentials of PtCu/C for CO oxidation show a negative shift of ca. 70 mV. More significantly, PtCu/C shows high stability in the acid solution, which can maintain 90.1% retention in ECSA after 1000 CV cycles. In addition, the solid separation method offers ease of manipulation, allowing the synthesis of a novel class of highly dispersed binary metal nanoparticles.